How reading changed my life - Quindlen, Anna (The library of contemporary thought., 1998)
Pulitzer Prize-winning columnist and bestselling author Anna Quindlen uses the mastery of the medium in which she works to send an utterly compelling message as she explores the importance of books in her life and their vital role in society. THE LIBRARY OF CONTEMPORARY THOUGHT is a groundbreaking series where America's finest writers and most brilliant minds tackle today's most provocative, fascinating, and relevant issues. Striking and daring, creative and important, these original voices on matters political, social, economic, and cultural, will enlighten, comfort, entertain, enrage, and ignite healthy debate across the country.